2022
DOI: 10.1007/s11367-022-02025-0
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of behind-the-meter Bitcoin mining at US power plant

Abstract: Purpose Due to its highly energy-intensive process, Bitcoin has attracted the global attention of climate research and media. At the time of this submission, behind-the-meter Bitcoin mining has gained significant traction; however, not a single environmental impact assessment has been conducted on this type of operation. This study seeks to fill the gap, applying the established Life Cycle Assessment methodology to estimate the environmental footprint of a single case study. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In June 2022, the gas-fired Greenidge power plant, at Seneca Lake, N.Y., U.S.A., was denied a permit renewal to operate since the significant fraction (up to 55%) of its power output has been used for behind-the-meter bitcoin mining. 45,46 Naturally, exploitation of fossil fuels to power bitcoin mining is questionable and experiences regulatory pressure. Originally a coal-fired facility, Greenidge was recommissioned in 2017 as a natural gas power plant and since 2020 utilized bitcoin mining to monetize off-peak periods, during which they struggled to sell electricity to the grid at a profit.…”
Section: Renewable Energymentioning
confidence: 99%
“…In June 2022, the gas-fired Greenidge power plant, at Seneca Lake, N.Y., U.S.A., was denied a permit renewal to operate since the significant fraction (up to 55%) of its power output has been used for behind-the-meter bitcoin mining. 45,46 Naturally, exploitation of fossil fuels to power bitcoin mining is questionable and experiences regulatory pressure. Originally a coal-fired facility, Greenidge was recommissioned in 2017 as a natural gas power plant and since 2020 utilized bitcoin mining to monetize off-peak periods, during which they struggled to sell electricity to the grid at a profit.…”
Section: Renewable Energymentioning
confidence: 99%
“…Note that fossil energy subsidies, which artificially undercut This does not completely exclude forms of decarbonizing regulatory unfriendliness. For instance, Roeck and Drennen [13] argue that miners should be forced to maintain a high renewable content to drive miners into greener areas ("carbon leakage").…”
Section: Regulation and Public Outcrymentioning
confidence: 99%
“…In this regard, the state of the art is limited. Although many have sought to estimate Bitcoin's carbon footprint (see II), only a limited number of papers have put their focus in bitcoin and flexible load response [13], [14]. The work is still in embryonic stages, highly contested and not systematized.…”
Section: B Flexible Load Response Through Cryptocurrency Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Mora et al (2018) mentioned in their study that if the adoption of Bitcoin increases, global warming will create an electricity demand that will cause an increase of 2 °C in the next ten years. Köhler and Pizzol (2019) and Roeck and Drennen (2022) claimed that Bitcoin mining increases energy consumption and consequently threatens climate change mitigation practices. Mohsin et al, (2020) concluded that there is a bidirectional causality relationship between the VECM model and the volume of cryptocurrencies and environmental degradation in the short and long run.…”
Section: Literaturementioning
confidence: 99%